2002
DOI: 10.1097/00006223-200201000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Nurse Graduate Leadership Outcomes

Abstract: Readiness for professional nursing practice in the current diverse and complex healthcare environment requires leadership capabilities. Faculty are challenged to identify specific leadership capabilities needed by graduate nurses upon entry into professional practice and to develop models from which they can accurately and authentically assess their demonstration. This article presents the development and implementation of an innovative leadership outcome assessment model. The model was developed in collaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…There appears to be insufficient human capacity in research as well as few research mentors and role models, and a lack of a research culture, which can have a negative impact on research output in HPE institutions in lowincome countries. Thus, although there is a significant Table 3 Assessment models, frameworks, type, approach and methods and study sample [23][24][25][26][27][28][29][31][32][33][34][35] NB: Grey scale sections were not reported amount of innovation taking place in HPE institutions in LMICs, there is still limited research output. There also seems to be insufficient networking among research communities in LMICs, meaning that support among researchers is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There appears to be insufficient human capacity in research as well as few research mentors and role models, and a lack of a research culture, which can have a negative impact on research output in HPE institutions in lowincome countries. Thus, although there is a significant Table 3 Assessment models, frameworks, type, approach and methods and study sample [23][24][25][26][27][28][29][31][32][33][34][35] NB: Grey scale sections were not reported amount of innovation taking place in HPE institutions in LMICs, there is still limited research output. There also seems to be insufficient networking among research communities in LMICs, meaning that support among researchers is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the aim of the studies, half of the articles (n = 7) reported on the implementation of assessment models that were utilised in their institutions [22][23][24][25][26][27][28]. The other articles (n = 7) reported on the development of, or proposal to develop assessment models to be implemented [29][30][31][32][33][34][35].…”
Section: Contextual Backgroundmentioning
confidence: 99%
“…The predicable day is also described by Wissmann, Hauck and Clawson (2002) and is used as a means of assessing leadership. In this research, nurses reported that they used the benchmark of a predictable day as a means of determining the degree to which students could manage a workload and for taking into account the challenges of the practice environment.…”
Section: '…They [Assessors and Preceptors] Need To Have Knowledge And Experience To Know What Is Acceptable You Couldn't Get Just Anymentioning
confidence: 99%
“…While there had been a number of publications in recent years, the majority of these focus on: characteristics of competence and measurement issues (Exstrom, 2001;Hardcastle, 1999;Waddell, 2001;Watson, Stimpson, Topping, & Porock, 2002;Zhang, Luk, Arthur & Wong, 2001); standards of competence, specialty areas and advanced practice (Badger & Rawstorne, 1998;Barker, Williams & Smith, 2001, Darbyshire, 1994ICN, 2002;O'Brien, O'Brien, McNulty, Morrison-Ngatai, Skews, Ryan, Hardy, Gaskin & Boddy, 2002;Wissmann, Hauck & Clawson, 2002); and assessment methods and measurement of student nurse clinical performance (Andre, 2000;Horsburgh, 2000;Neary, 2001;Robb, Fleming & Dietert, 2002). Others (French, 2002;May, Edell, Butell, Doughty & Langford, 1999;Maynard, 1996;White & Taylor, 2002) discussed the link between evidencebased practice, critical thinking, nursing knowledge and competency to practice; or Chapter 1: Introduction the educational preparation of nurses and the performance of the graduate nurse (Bechtel, Davidhizar & Bradshaw, 1999;Chapman, 1999;Fulbrook, Rolfe, Albarran & Boxall, 2000;Grundy, 2001;Meerabeau, 2001;Watson, 2002).…”
Section: The Significance Of the Studymentioning
confidence: 99%